1984
DOI: 10.1515/text.1.1984.4.1-3.249
|View full text |Cite
|
Sign up to set email alerts
|

Challenge and control in lawyer-client interaction: A case study in an Israeli Legal Aid office

Abstract: In contrast to the traditional depiction of lawyers äs providing loyal disinterested Service to clients, analysis of one lawyer-client interaction in a legal aid office revealed that the lawyer used language to control the dient's presentation of the case t and to define it in terms of convenience to the organization rather than the expressed wishes of the dient. Three types of linguistic strategies relating to the control oftalk were examined: (l) management of structural features; (2) choice of instrumentali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 12 publications
1
21
0
1
Order By: Relevance
“…The most common way of exercising this interpretational privilege is for judges and lawyers to make so-called reformulations (Bogoch and Danet, 1984;Thomas, 1985;'formulations' in Heritage and Watson, 1980). Here are some examples (marked by *):…”
Section: Topic Regulation and The Negotiation Of Meaningmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common way of exercising this interpretational privilege is for judges and lawyers to make so-called reformulations (Bogoch and Danet, 1984;Thomas, 1985;'formulations' in Heritage and Watson, 1980). Here are some examples (marked by *):…”
Section: Topic Regulation and The Negotiation Of Meaningmentioning
confidence: 99%
“…A substantial part of it has been concerned with constraints on the contributions by witnesses and defendants. The issue of how different kinds of questions constrain answers in court is an old one (cf., e.g., Muscio, 1915), which has received a great deal of attention lately (Bogoch and Danet, 1984;Danet et al, 1976;Danet and Bogoch, 1980;Harris, 1984;Philips, 1984;Thomas, 1985;Woodbury, 1984). Other studies have demonstrated additional aspects of the fact that judges and lawyers act out of a position of power (Atkinson, 1982;Ceasar-Wolf, 1984;Drew, 1985;Wodak-Engel, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…O' Barr 1982, Danet 1984, and the New Zealand context (Lane 1988 ). This article expands the picture by looking at all the uses of well by all participants in the examination phases of trials.…”
Section: Introductionmentioning
confidence: 99%
“…Lawyers have been shown to restrict the engagement of clients to the provision of factual information, limit discussion to a narrow focus on legal issues, only involve clients in decision-making when it is absolutely necessary, and present a limited range of options (e.g. Blumberg, 1967;Skolnick, 1967;Rosenthal, 1974;Hosticka, 1979;Bogoch & Danet, 1984;Simon, 1988;Mather et al, 1995;McConville & Mirsky, 1995;Pepper, 1995;Michelson, 2006;Kozin, 2007;Melville & Laing, 2008, 2010.…”
Section: Introductionmentioning
confidence: 99%